“Cracking the Stone”: The Long History of Capitalist Crisis and Toronto’s Dispossessed, 1830–1930 - Palmer, Bryan; Heroux, Gaetan (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2012)
What constitutes proletarianization? The conventional answer to this seemingly simple question often stresses waged labour. Yet many workers, past and present, are routinely unable to secure paid employment, in part because of the persistence of capitalist crises of various kinds. This study of indigent workers in Toronto from the 1830s to the 1930s is premised on an understanding of proletarianization as dispossession, on the one hand, and, on the other, of the ways in which capitalism necessarily produces recurrent crises, leaving many workers wageless. It addresses how wagelessness and poverty were criminalized through the development of institutions of ostensible charitable relief, such as the Toronto House of Industry, in which those seeking shelter and/or sustenance were required to chop wood or, more onerously, break stone in order to be admitted to the ranks of those ‘deserving’ of such support. By the end of the nineteenth century-resistance to such “labour tests” was increasingly evident. Protests took place in Toronto, where the black flag was carried in demonstrations demanding “work or bread.” Refusing to “crack the stone” and demands that relief be administered differently were common features of mobilizations of the wageless in the opening decades of the twentieth century, in which socialists often took the lead. By the time of capitalism’s devastating collapse in the Great Depression of the 1930s, Toronto’s wageless were well situated to mount an outcasts’ offensive.